2019
DOI: 10.1101/830794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blood RNA Signatures Predict Recent Tuberculosis Exposure in Mice, Macaques and Humans

Abstract: Tuberculosis (TB) is the leading cause of death due to a single infectious disease.Knowing when a person was infected with Mycobacterium tuberculosis (M.tb) is critical as recent infection is the strongest clinical risk factor for progression to TB disease in immunocompetent individuals. However, time since M.tb infection is challenging to determine in routine clinical practice. To define a biomarker for recent TB exposure, we determined whether gene expression patterns in blood RNA correlated with time since … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…This would be an extraordinarily large study to conduct, since on a population level only a minority of individuals who acquire M.tb infection progress to disease [44]. Further, limited sample availability prevented us from testing other recently described biomarkers, such as those based on T cell proliferation [32] or gene expression [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would be an extraordinarily large study to conduct, since on a population level only a minority of individuals who acquire M.tb infection progress to disease [44]. Further, limited sample availability prevented us from testing other recently described biomarkers, such as those based on T cell proliferation [32] or gene expression [33].…”
Section: Discussionmentioning
confidence: 99%
“…Other functional assays that measure M.tbspecific T cell properties such as Th1 cytokine co-expression profiles [27,28], T cell differentiation (CD27, [29,30]) and T cell activation [17][18][19][20][21][22] have been proposed as new potential immunodiagnostic concepts that can distinguish between M.tb infection and disease. In line with this principle, potential biomarkers of recent M.tb infection based on proportions of TNF-only (IFN--IL-2-) TE (CD45RA-CCR7-CD127-) CD4 T cells or T cell proliferation, as well as a blood transcriptomic signature, have been described [31][32][33]. Halliday and colleagues demonstrated that the proportion of PPD-reactive TNF-only TE CD4 T cells was highest in tuberculosis patients and lowest in individuals with remote M.tb infection, and distinguished between recent and remote M.tb infection with a sensitivity and specificity of 89% and 65%, respectively [31].…”
Section: Introductionmentioning
confidence: 91%
“…We thank L. Schlesinger and L. Barreiro for critical review of the manuscript. This manuscript has been released as a Pre-Print at bioRxiv 73 .…”
Section: Acknowledgementsmentioning
confidence: 99%